Pengaruh Live Streaming dan Review Influencer terhadap Keputusan Pembelian Pengguna Tiktok Shop - Ratnaningrum, Nenci Mukti; Sari, Dewi Kartika; Herwandito, Seto (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aimed to examine the influence of the live streaming feature and influencer reviews on TikTok Shop users' purchasing decisions. The study focused on students at Satya Wacana Christian University (UKSW) in Salatiga, known for their active use of digital media. TikTok Shop, as a form of social commerce, offers a combination of interactive content and public figure involvement to build consumer perceptions. The research methodology employed a quantitative approach, distributing questionnaires to 390 respondents selected using a purposive sampling technique. The collected data were analyzed using multiple linear regression to examine the extent to which the two independent variables simultaneously or partially influenced purchasing decisions. The analysis showed that the live streaming feature and influencer reviews had a positive and significant impact on purchasing decisions, both when tested separately and together. These findings confirm that digital marketing communication strategies that prioritize content interactivity and social trust play a significant role in influencing consumer behavior, particularly among the younger generation. Furthermore, this research contributes to the development of academic studies in the field of digital marketing communication, while providing practical implications for businesses and influencers in developing more effective promotional strategies in the digital era.